Role of Ocimum basilicum var. thyrsiflora (Thai Basil) Aqueous Extract Treated with Yeast Suspension in Enhancing Tomato Plant Resistance to Fusarium oxysporum - Wurood Hantoosh Neamah; Shatha Fadel Abdel sayed; Fatimah Ali Hasan (Universitas Sebelas Maret, 2023)
Tomato (Solanum lycopersicum L.) is the most popular vegetable crop in the world. It is grown almost all over the world. The biggest challenge in producing this crop is diseases caused by Fusarium oxysporum. In developing eco-friendly antifungal selective substances for controlling Fusarium diseases, the role of Ocimum basilicum var. thyrsiflora (Thai basil) aqueous extract against stimulated F. oxysporum was studied in vivo. The presoaked tomato seeds with yeast-treated and untreated O. basilicum var. thyrsiflora extracts were cultivated in F. oxysporum-infused soil. This part investigated the recovery role of these botanical extracts against the Fusarium infection on tomato plants, especially on its growth and biochemical traits. The research showed that the vegetative and floral growth parameters of plant decreased significantly due to F. oxysporum infection. The pigment contents, including carotenoids, β-carotene and lycopene in tomato fruits, were also passively affected by fungus infection at variance to phenolic and flavonoid content. Moreover, the O. basilicum var. thyrsiflora extract presoaked seeds remarkably enhanced the growth parameters of plant and the fruit pigment content. There was no significant difference in fungus infection recovery between infected plants that got yeast-treated extract and infected plants that got yeast-untreated extract. However, the pathogen inhibition percentage with extract from yeast-treated Thai basil plants in vitro increased. This research showed that utilizing O. basilicum var. thyrsiflora extract to control F. oxysporum infection of tomato plants was possible and available.